2002
DOI: 10.1897/1551-5028(2002)021<1198:pfdant>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Postexposure Feeding Depression: A New Toxicity Endpoint for Use in Laboratory Studies With Daphnia Magna

Abstract: In situ bioassays with daphnids currently employ lethality as an endpoint, and although sublethal responses (reproduction and feeding rate) can be measured in the field, such endpoints pose major practical challenges. Previous studies have indicated that Daphnia magna exposed to toxic substances can exhibit delayed recovery in feeding behavior (postexposure feeding depression). This simple, robust response has the potential to be an ecologically relevant and potentially diagnostic endpoint. This study develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(110 citation statements)
references
References 22 publications
7
103
0
Order By: Relevance
“…This assumption corresponds fully with available literature on daphnids and pyrethroids (Day and Kaushik 1987b;Day et al 1987c;McWilliam and Baird 2002;Christensen et al 2005;Reynaldi et al 2006). Due to this effect on assimilation, strong effects were observed on growth curves, which were immediately translated to a delayed onset of reproduction, thereby ultimately affecting the reproduction curves (Fig.…”
Section: Mode Of Action Of Fvsupporting
confidence: 85%
“…This assumption corresponds fully with available literature on daphnids and pyrethroids (Day and Kaushik 1987b;Day et al 1987c;McWilliam and Baird 2002;Christensen et al 2005;Reynaldi et al 2006). Due to this effect on assimilation, strong effects were observed on growth curves, which were immediately translated to a delayed onset of reproduction, thereby ultimately affecting the reproduction curves (Fig.…”
Section: Mode Of Action Of Fvsupporting
confidence: 85%
“…Pulp mill effluents are composed of several substances among which polycyclic aromatic hydrocarbons (McLeay 1987). In a study on the applicability of a postexposure feeding test with D. magna for toxicity assessments, McWilliam and Baird (2002) found that the polycyclic aromatic hydrocarbon fluoranthene only induced feeding depression during exposure and not during the postexposure feeding period.…”
Section: Discussionmentioning
confidence: 99%
“…The D. magna postexposure feeding test was based on the methodology developed by McWilliam and Baird (2002). This test was adopted in the present study because pulp mill effluents contain suspended solids and particulates that may influence the feeding rate.…”
Section: Toxicity Testsmentioning
confidence: 99%
“…Food is the basic requirement for growth and other physiological functions of the body [22]. Feeding rate has been proposed in several studies as a sensitive indicator of toxic stress in both freshwater and marine species [23][24][25].…”
Section: Effects Of Pesticides and Antibiotics In Penaeid Shrimpmentioning
confidence: 99%